Sensitive and Accurate Determination of Bisphenol A Using Dispersive Liquid-Liquid Microextraction and Gas Chromatography-Mass Spectrometry - Demirel, Maruf Hursit (Taylor & Francis Inc, 2026)
Water and food safety have become increasingly important in recent years. Endocrine disrupting compounds, such as Bisphenol A (BPA) and other chemicals, mimic natural hormones and cause hormonal imbalances, leading to various health disorders. This study proposes straightforward, accurate, and sensitive dispersive liquid-liquid microextraction (DLLME) for the preconcentration of BPA before its determination by gas chromatography-mass spectrometry (GC-MS). Critical parameters affecting the extraction efficiency were optimized, including the type and amount of extractant solvent, the type and amount of dispersant solvent, buffer pH, and salt effect. The detection and quantification limits for BPA were 0.54 and 1.80 ng/mL, respectively. Calibration plot for BPA demonstrated good linearity. Recovery studies conducted with spiked bottled natural spring water and iced tea samples yielded recoveries of 91 and 97%, respectively. Various commercial demijohn and polyethylene terephthalate (PET) bottled spring water, PET and tin cola, soda, and fruit juice samples were analyzed using the optimized method.
Keywords: Bisphenol A; Bottled Spring Water; Dispersive Liquid-Liquid Microextraction (Dllme); Endocrine Disrupter; Gas Chromatography-Mass Spectrometry (Gc-Ms)